The effect of childhood trauma on complex posttraumatic stress disorder: the role of self-esteem - Yichu Li; Yiming Liang (European Journal of Psychotraumatology, 2023)
ABSTRACTBackground: Due to the short time that complex posttraumatic stress disorder (CPTSD) has been an independent diagnosis, few studies have explored the role that self-esteem might play in the relationship between childhood trauma and CPTSD.Objective: The current study aimed to explore the impact of childhood trauma on CPTSD and the role of self-esteem in this relationship.Methods: Study 1 involved a questionnaire survey in which a total of 360 young Chinese adults with childhood trauma participated. Study 2 used experimental research by manipulating short-term self-esteem to explore the effect of self-esteem on CPTSD. A total of 80 young Chinese adults with childhood trauma participated.Results: The results of Study 1 showed that childhood trauma positively predicts adulthood CPTSD, while self-esteem partially mediates the relationship between the two. It also found that self-esteem has a greater mediating effect on the disordered self-organization (DSO) dimension of CPTSD than on the PTSD dimension. In Study 2, participants in the high manipulated-self-esteem group reported fewer CPTSD symptoms than those in the low manipulated-self-esteem group.Conclusion: Overall, this study emphasized the role of self-esteem in CPTSD among individuals with a childhood trauma history. In practice, we provided a potential optimization direction for CPTSD clinical treatment, suggesting a method of self-esteem reconstruction.